RURAL HEALTH CARE SYSTEM IN THE ERA OF COVOD-19: A STUDY FROM MURSHIDABAD (WEST BENGAL - Md Sahidul Islam, Ravindra Kumar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Due to Covid-19 led lockdown, people had faced tremendous challenges in respect to health and livelihoods. No doubt lockdown hits every sphere of life from both rural and urban areas. This paper argues people from rural areas has suffered most than urban areas in respect to access to health care. Building on the primary data set, this paper intends to understand the extent to inaccessibility to public health care service due to Covid-19 led lockdown in rural Bengal. The data has been collected from 88 patients who had come for treatment to out patient door in Murshidabad Medical College and Hospital, West Bengal during lockdown period.The result indicated increasing out of pocket expenditure due to inaccessibility to public health care system and they had to resort to nearby by quacks including rural medical practitioners since there was no provision for commutation to public health care institutions. Thereby, as learning from this pandemic, it is suggested to strengthen and enhance the efficacy of rural health care public institutions that already have been there.